Lettered Christians : Christians, letters, and late antique Oxyrhynchus - Blumell, Lincoln H. 1975- (New Testament Tools, Studies and Documents, 2012)
With the discovery of the Oxyrhynchus Papyri just over a century ago a number of important texts directly relating to ancient Christianity have come to light. While certain literary texts have received considerable attention in scholarship by comparison the documentary evidence relating to Christianity has received far less attention and remains rather obscure. To help redress this imbalance, and to lend some context to the Christian literary materials, this book examines the extant Christian epistolary remains from Oxyrhynchus between the third and seventh centuries CE. Drawing upon this unique corpus of evidence, which until this point has never been collectively nor systematically treated, this book breaks new ground as it employs the letters to consider various questions relating to Christianity in the Oxyrhynchite. Not only does this lucid study fill a void in scholarship, it also gives a number of insights that have larger implications on Christianity in late antiquity.